Buy Now, Regret Later? Unpacking the Role of Risk Perception in the Nexus between PayLater Usage, Hedonic Lifestyle, and Consumptive Behavior among Generation Z in Lampung City - Anita; Afrizal Afit (Journal of Management and Business Innovation, 2026)
This study aims to examine the influence of PayLater usage and hedonic lifestyle on consumptive behavior, with risk perception as a mediating variable among Generation Z in Lampung City. This research employs a quantitative approach using a survey method with 318 respondents selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. This study extends consumer behavior literature by integrating financial technology usage and psychological factors into a mediation model. It highlights the role of risk perception as a cognitive mechanism linking PayLater usage and hedonic lifestyle to consumptive behavior. The results reveal that PayLater usage and hedonic lifestyle significantly increase consumptive behavior, while risk perception negatively affects it. Risk perception partially mediates these relationships. The findings suggest the need for financial education and risk awareness programs to mitigate excessive consumption among Generation Z. This study is limited by its cross-sectional design and specific population context. Future research should consider longitudinal approaches and additional variables.